Anxiety among people living with HIV/AIDS on antiretroviral treatment attending tertiary care hospitals in Lucknow, Uttar Pradesh, India - Shukla, Mukesh; Agarwal, Monika; Singh, Jai Vir; Srivastava, Anand Kumar (International Journal of Research in Medical Sciences, 2017)
Background: One of the major health challenges faced by India is the rapid growth of HIV/AIDS and its impact upon human life. Co-morbidities like anxiety are often overlooked while providing ART services to HIV/AIDS patients. Therefore the present study was conducted to assess the anxiety and associated factors among PLHA (People Living with HIV/AIDS) on antiretroviral treatment attending tertiary care hospitals in Lucknow. Methods: Hospital‑based cross-sectional study was conducted from November 2013 to March 2014 among 170 patients on treatment attending antiretroviral therapy (ART) centre of two tertiary care hospitals of Lucknow. Systematic random sampling was used to recruit patients. The anxiety level of all included patients was scored as per Hamilton anxiety rating scale. Results: The mean HAM-A score of 179 patients was 10.74±6.04. Majority (92.1%) of the patients had HAM-A score less than 17 indicating mild severity, 5.0% of the patient had mild to moderate severity while only 2.7% had moderate to severe level of anxiety symptoms. None of the patient had very severe level of anxiety. Significant association was found between level of anxiety symptoms with educational status (0.03), perception of side-effects during last one month (0.03) and duration of treatment (0.04). Conclusions: People living with HIV/AIDS need to be periodically educated and informed about various issues associated with the disease severity and antiretroviral treatment along with its side-effects so that they could better cope with disease and its treatment outcomes over time and be able to seek early treatment accordingly.